Determinasi Income Smoothing: Profitabilitas, Risiko Keuangan, Dan Nilai Perusahaan - Radiyanti, Amanda Nata; Susilawati, Susi; Samukri, Samukri; Suryaningsih, Maria (E-Jurnal Akuntansi, 2022)
The practice of income smoothing can arise due to dysfunctional behavior between various parties with an interest in the company's financial statements. The study was conducted to find out empirical evidence of the factors that influence income smoothing in companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The number of samples is 88 companies and taken by simple random sampling method. The data analysis used is panel data regression analysis. The results showed that financial risk had a negative effect on income smoothing. Meanwhile, profitability and firm value have no effect on income smoothing. Keywords: Profitability; Financial Risk; Firm Value; Income Smoothing.